2010
DOI: 10.1001/archgenpsychiatry.2010.10
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synaptic Dopamine Function in Associative Regions of the Striatum in Schizophrenia

Abstract: These findings suggest that schizophrenia is associated with elevated dopamine function in associative regions of the striatum. Because the precommissural dorsal caudate processes information from the dorsolateral prefrontal cortex, this observation also suggests that elevated subcortical dopamine function might adversely affect performance of the dorsolateral prefrontal cortex in schizophrenia. On the other hand, the absence of a group difference in the limbic striatum brings into question the therapeutic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
359
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 480 publications
(396 citation statements)
references
References 80 publications
31
359
3
Order By: Relevance
“…This is at least prima facie consistent with the notion that increased dopaminergic activity in the striatum should also result in greater glutamatergic activity therein. This also mirrors the findings in persons with schizophrenia, wherein both increased striatal dopamine and striatal glutamate levels are observed compared to healthy controls; albeit in the dorsal striatum (Caravaggio et al, 2015;Kegeles et al, 2010). However, a negative correlation was observed between glutamate concentrations in the left prefrontal cortex and dopamine synthesis capacity in the left ventral striatum (r 2 = .17).…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…This is at least prima facie consistent with the notion that increased dopaminergic activity in the striatum should also result in greater glutamatergic activity therein. This also mirrors the findings in persons with schizophrenia, wherein both increased striatal dopamine and striatal glutamate levels are observed compared to healthy controls; albeit in the dorsal striatum (Caravaggio et al, 2015;Kegeles et al, 2010). However, a negative correlation was observed between glutamate concentrations in the left prefrontal cortex and dopamine synthesis capacity in the left ventral striatum (r 2 = .17).…”
Section: Introductionsupporting
confidence: 84%
“…Consistent with the basal ganglia model, persons with cocaine addiction have also been observed to have less glutamate-to-creatine in the rostral anterior cingulate (Yang et al, 2009), and less glutamateto-glutamine in the dorsal anterior cingulate (Yucel et al, 2007) In patients affected by schizophrenia, it has been demonstrated with PET that there is more endogenous dopamine occupying D 2/3 R in the dorsal caudate (Caravaggio et al, 2015;Kegeles et al, 2010). In accordance with the classical model, it has been demonstrated with 1 HMRS that persons at ultra-high risk for psychosis (characterized by sub-threshold psychotic symptoms, a high likelihood of a family history of schizophrenia, and a decline in everyday functioning) and patients with a first episode of psychosis have increased glutamate levels in the dorsal caudate compared to healthy controls (de la Fuente-Sandoval et al, 2013a,b;de la Fuente-Sandoval et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Studies have also suggested an increased affinity of D 2 receptors for DA in schizophrenia, that may produce a D 2 receptor supersensitivity in the NAc contributing to psychosis [79]. Additionally, a PET study found higher synaptic DA concentrations in the ventral striatum in schizophrenia [425]. …”
Section: Reviewmentioning
confidence: 99%